Unraveling the Lhasa‐Qiangtang Collision in Western Tibet: Insights From Geochronological and Paleomagnetic Analyses - Peiping Song; Lin Ding; Jinxiang Li; Yahui Yue; Jing Xie (Geophysical Research Letters)
Abstract The Lhasa‐Qiangtang collision closed the Meso‐Tethys Ocean, but the exact timing of this event remains hotly debated. Here, we present geochronological and paleomagnetic analyses conducted on Cretaceous volcanics from western Qiangtang to constrain the Lhasa‐Qiangtang collision in western Tibet. Our investigations yield a paleolatitude of ∼30.5 ± 5.0°N for western Qiangtang during ca. 110–100 Ma. A reanalysis of previously acquired Mesozoic‐Cenozoic paleomagnetic data from western Qiangtang suggests a stationary position during ca. 136–34 Ma. Examination of paleomagnetic data from western Lhasa reveals a significant reduction in northward paleolatitudinal motion during the Early Cretaceous, dropping from ∼12.3 cm/yr to nearly zero. Integration of our paleomagnetic findings with available geological records has led to conclude that the Lhasa‐Qiangtang collision in western Tibet occurred at ca. 132 Ma. Additionally, we infer that crustal shortening on the order of ∼1,000 km happened between Lhasa and Qiangtang during the Early Cenozoic.